Zapach śmierci, epilepsja i portret papieża ("Tatarak" Andrzeja Wajdy i "Bracia Karamazow" Petra Zelenki) - Wojciech Otto (Images)
The Smell of Heath, Epilepsy and the Pope’s Portrait (Andrzej Wajda’s “Sweet Rush” and Peter Zelenka’s “The Brothers Kramazov”)